The role of inflammatory theory in the pathogenesis of atrial fibrillation - K. V. Davtyan; A. A. Kalemberg; E. N. Tsareva; O. V. Blagova; M. S. Harlap (Российский кардиологический журнал, 2019)
Based on the data available in the literature, it is obvious that inflammation plays a significant role in the initiation, support and progression of AF. However, it is important that AF by itself is a factor provoking the development of inflammation in the atrial myocardium, which leads to the further progression of the disease according to the principle of “AF produces AF.” The question of the primacy of the development and correlations of process links is still not fully understood: does inflammation leads to fibrillation or does fibrillation leads to inflammation?The authors analyzed the data of the world literature and tried to describe the main concepts of the inflammatory theory of AF and the practical aspects of its application.